Victimological Study of Revenue State Losses Caused by Tax Crime - Ratnasari, Zela Dwi; Juanda, Juanda (Dinasti Publisher, 2023)
The victimology study on recouping state damages from criminal acts in tax crime is discussed in this essay. It is important to understand that the victim in tax criminal is the revenue state losses. The research method used is a juridical-empirical research method. The results of the study show that victims in a criminal incident are not always individuals, communities, legal entities, the private sector and the government. In cases of tax crime, the state must be given legal protection in accordance with the principles of benefit, fairness, balance, and legal clarity in the form of rules, legislation and specific practices both preventive and repressive in character that refer to the implementation of the protection of victims' rights. In order to maximize the recovery of losses on state revenues, tax investigators are given the authority to block and/or seize assets from taxpayers who do not use the ultimate remedy, allowing them to secure the early settlement of criminal fines. This is done by applying the principle of lex specialis derogate legi generali to Article 30 paragraph (2) of the Criminal Code.